Peryfrazy nazw własnych w aspekcie strukturalnym - Afeltowicz, Beata (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2020)
Broadly speaking, linguistic periphrase is the use of a complex descriptive expression instead of a single word. The subjects of the description in the article are poetic periphrases referring to the names of singing women. This general term is related to different types of singing activities, which can be done by: singers, vocalists, opera singers, divas, soloists, choristers, prima donnas, chancellors. The aim of the research was to collect a complete set of contemporary peripheral terms of Polish and foreign singing women, to analyse their structure in formal terms and to analyse the lexemes (14 reference units and 9 proper names) as constitutive elements of periphrases. The article includes an alphabetical index of personal names along with the descriptive expressions for them (over 60 analytical lexical units).